Achieving work-life balance in the National Collegiate Athletic Association Division I Setting, Part II: Perspectives from head athletic trainers - Goodman, A.; Mazerolle, S. M.; Pitney, W. A. (Journal of Athletic Training, 2015)
Context: Work-life balance has been examined at the collegiate level from multiple perspectives except for the athletic trainer (AT) serving in a managerial or leadership role.